Destination Image of Jordan - Asfar, Aya (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This research examines the perceived destination image of the Hashemite Kingdom of Jordan through the complex relationships between destination image components and their influence on intention to revisit and to recommend. Overall destination image operationalized with the cognitive, affective, and unique image components. A convenience sample of 250 tourists visiting Jordan was used. A structured questionnaire is developed to collect data. Using Spearman correlation test, the findings reveal significant positive correlations between Cognitive image and affective image and unique image and holistic image. However, intention to revisit and recommend were found to have moderate correlation with the three image components. Therefore, the study concludes that holistic image has to be created through cognitive, affective and unique images. Keywords: Jordan, destination image

ÖZ: Bu araştırma, Ürdün Haşimi Krallığı‘nın algılanan destinasyon imajını, destinasyon imaj bileşenleri ile tekrar ziyaret etme ve önerme niyetleri üzerindeki karmaşık ilişkiler kullanarak incemektedir. Genel Destinasyon imajı bilişsel, duyuşsal ve benzersiz görüntü bileşenleri ile ölçülmüştür. Veriler Ürdün'ü ziyaret eden 250 turistten anket yöntemi ile toplanmıştır. Spearman korelasyon testi sonuçlarına göre bilişsel imge ve duyuşsal imge ile benzersiz imge ve bütünsel imge arasında kuvvetli pozitif korelasyon bulunmuştur. Bununla birlikte, yeniden gözden geçirme ve tavsiye etme niyeti ile ilgili olarak orta düzeyde bir ilişki saptanmıştır. Bu nedenle çalışma, bilişsel, duyuşsal ve özgün imgeler yoluyla bütünsel imajın oluşturulması gerektiği sonucuna varmıştır. Anahtar Sözcükler: Afektif İmge, Bilişsel İmge, Benzersiz İmge, Bütünsel İmge.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Prof. Dr. Seldjan Timur.
Keywords: Business Administration; Marketing Management; Destination Image--Jordan; Jordan, destination image